(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2019)
The aim of the research is to demonstrate a new method of monitoring and evaluating performance, which is known as Balanced Scorecard with four axes: (financial axis, customer focus, internal operations axis, learning and growth axis) and its impact on strategic Management by combining financial performance measures with performance measures The research aims to show the most important uses of the Balanced Scorecard, which is not based on a specific aspect but rather measures performance in four axes. In order to achieve the objectives of the research, the researchers adopted the proposed new form, which includes the four previous axes. The answer is given to each axis by the competent authority within the economic unit, unlike the old form whose response was limited to quality management. In personal bias. The sample of the study is an effective service unit in the local health sector, Al Sadr Medical City in Najaf because of its important role in providing medical services in the province. The research has reached a number of analytical and theoretical results. By the management of the hospital while the focus of customers ranked fourth, and as a result, there is interest and focus on these four main axes, which indicates the holistic view of the activities of the Iraqi health sector in this area.